STRATEGI PEMASARAN PAKET WISATA DI BALI EASY HOLIDAY DENPASAR BALI - Kevin Perangin-Angin, Erick; Sudana, I Putu; Sudiarta, I Nyoman (Jurnal IPTA (Industri Perjalanan Wisata); Vol 5 No 1 (2017): Jurnal IPTA (July 2017)DO - 10.24843/IPTA.2017.v05.i01.p01)
This Journal aimed to know the strengths and weaknesses of the internal environment and opportunities as well as threats from the external environment and create strategies and marketing programs that can be applied in the Bali Easy Holiday. The technique data collection using observation, interview, questionnaire, the study of literature and documentation study. Sampling techniques using a purposive sampling. Data analysis techniques using qualitative descriptive analysis and Likert scale analysis. The results of this research are obtaining indicators of strengths and weaknesses of internal environment and the opportunities and threats of weaknesses in Bali Easy Holiday. Bali Easy Holiday gains 16 indicators of strengths and 4 indicators of weaknesses in Bali Easy Holiday. Bali Easy Holiday gains 9 indicators of opportunities 5 indicators of threats in Bali Easy Holiday. Marketing strategies can be applied to Bali Easy Holiday, namely : the creation of strategy and product development, market development strategies, promotion strategy, a strategy of improved human resources, the strategy of market penetration strategies, improvement of the quality of products and services and pricing strategies. This research has some advice for Bali Easy Holiday is to increase the intensity of promotion, provide ease reservations and payments to consumers, renew tour packages, provide affordable rates to customers and formed a marketing division.
Keywords: Marketing Strategy, Tour Package, Bali Easy Holiday